2012
DOI: 10.1186/1752-1947-6-325
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous evacuation of diffuse pulmonary interstitial emphysema by lung puncture in a baby with extremely low birth weight: a case report

Abstract: IntroductionPulmonary interstitial emphysema is a serious complication of mechanical ventilation and can become life-threatening if progression occurs. Therapeutic lung puncture is a treatment option for severe pulmonary interstitial emphysema but has a limited use in babies with extremely low birth weight. We present a case of pulmonary interstitial emphysema in a Japanese baby (1-day-old) boy with extremely low birth weight. The emphysema was successfully decompressed by therapeutic lung puncture performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(14 reference statements)
0
2
1
Order By: Relevance
“…As for the device, we could not clarify but 24-gauge peripheral intravenous catheter might have been used. 14 The infant in our case had considerably smaller weight compared with those previously reported cases of drainage. Further research is required to determine the optimum approach for this procedure in terms of adequate patient's condition, concrete device, and appropriate suction pressure.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…As for the device, we could not clarify but 24-gauge peripheral intravenous catheter might have been used. 14 The infant in our case had considerably smaller weight compared with those previously reported cases of drainage. Further research is required to determine the optimum approach for this procedure in terms of adequate patient's condition, concrete device, and appropriate suction pressure.…”
Section: Discussioncontrasting
confidence: 46%
“…2,[7][8][9][10][11][12] Conversely, there are a few case reports on percutaneous drainage for PIE. 13,14 The cause of PIE is leaked gas trapped in the interstitium from alveoli. 5 Especially, preterm infants have a higher risk of PIE as their perivascular connective tissues are abundant and relatively more compliant.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports to describe percutaneous catheter insertion as treatment of PIE, especially in ELBW infants. Milligan, et al 15 described that 75% of premature infant with PIE were treated by chest tube insertion, Watanabe, et al 16 reported an ELBW infant (420 g) whose diffuse PIE was evacuated. And Fujii and Moulton 17 reported ELBW infant (533 g) with PIE treated by pigtail catheter insertion into pneumatocele and chest tube to pleural cavity.…”
Section: Discussionmentioning
confidence: 99%